A novel high-temperature solar chemical reactor for syngas production from solar-driven thermochemical gasification of wood biomass - Sylvain Rodat; Quentin Bellouard; Stphane Abanades; Srirat Chuayboon; Pierre-Eric Frayssines; Serge Ravel (My University, 2018)
Solar energy is the most abundant renewable energy source on earth and its contribution in the energy mix is growing fast, especially for electricity production via photovoltaic panels and to a lesser extent for concentrated solar energy. However, concentrated solar energy can also provide high temperature heat for process applications. Solar fuels are envisioned as alternative fuels that would enable long term storage and transport of solar energy. Solar thermochemical gasification of lignocellulosic biomass has been investigated in this objective. The use of concentrated solar energy as the external heat source for the high-temperature reaction allows producing high-value syngas with both higher energy conversion efficiency and reduced cost of gas cleaning and separation, while saving biomass feedstock. A 1.5 kWth solar reactor was successfully tested for continuous solar driven gasification of millimetric wood particles under real solar irradiation using a parabolic dish concentrator. Investigated temperatures ranged from 1100°C to 1400°C. The influence of temperature, oxidizing agent nature (H2O or CO2), heating configuration (direct or indirect irradiation), on gas yield and energy conversion efficiency was investigated. The syngas yield drastically increased with the temperature for both steam and CO2 gasification, while increasing the steam content favored H2 production over CO. Continuous biomass conversion was demonstrated with a global solar-to-fuel energy conversion efficiency of 26% at 1300°C and a cold gas efficiency as high as 1.16, confirming efficient solar up-grade of the feedstock energy content.
Keywords: Chemical energy; Thermochemical Biomass Conversion Processes